The wider roles of science and innovation - Gluckman, Peter (New Zealand Science Review, 2011)
​The title of my talk is a little disconcerting, for I am not certain that we can or should try to dichotomise between the various roles of science and innovation in our society. A healthy and smart nation needs knowledge to pervade every aspect of its activities, and no society can meet its citizens’ objectives with-out greater economic prosperity. Indeed economic prosperity, social development and environmental protection are intimately intertwined. It is nonsensical to think in terms of a science and innovation ecosystem that does not recognise these intimate linkages. Those countries that have increased their investment in both the science and innovation ecosystems in the last thirty years are now much more productive than we are.